I survived the sinking of the Titanic, 1912 - Ball, Georgia; Gervasio; Tarshis, Lauren; Haus Studio (New York, NY Graphix, an imprint of Scholastic Inc., 2020)
Excited to board the Titanic with his aunt and little sister, ten-year-old George begins to explore the ill-fated ship's first-class storage cabin when the ship is rocked by a collision with an iceberg and begins to sink.
Based on: I survived the sinking of the Titanic, 1912 / Lauren Tarshis.
Includes bibliographical references.
School Library Journal, December 2019
Kirkus Review, November 2019
Library Media Connection starred, January 2020
School Library Journal
Keywords: Titanic (Steamship) -- Comic books, strips, etc. -- Juvenile fiction; Titanic (Steamship) -- Fiction; Titanic (Steamship) -- Comic books, strips, etc. -- Fiction; Ocean travel -- Comic books, strips, etc. -- Juvenile fiction; Shipwrecks -- Comic books, strips, etc. -- Juvenile fiction; Ocean travel -- Fiction; Shipwrecks -- Fiction; Cartoons and comics; Ocean travel -- Comic books, strips, etc. -- Fiction; Shipwrecks -- Comic books, strips, etc. -- Fiction